PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA BAGI HASIL (DBH), DAN FISCAL STRESS TERHADAP TINGKAT KEMANDIRIAN DI PROVINSI KALIMANTAN SELATAN - ARYADHANI PRASETYO; DEWI RAHAYU (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Aryadhani Prasetyo (2019). “Effects of Regional Original Revenue, General Allocation Funds, Profit Sharing Funds, and Fiscal Stress on the Level of Independence in the Province of South Kalimantan”. Advisor: Dr. Dewi Rahayu, SE, MP.This research was conducted to (1) analyze the effect of Regional Original Revenue, General Allocation Funds, Profit Sharing Funds and Fiscal Stress that affect the level of independence both simultaneously and partially in the Province of South Kalimantan; (2) to analyze what are the most dominant variables affecting the level of independence in the province of South Kalimantan.The data obtained in this study is from the official website of the South Kalimantan Provincial Government, namely the Central Kalimantan Statistics Agency, which deals with deals with the South Kalimantan Provincial Government Financial Report and the 2002-2016 Budget Realization Report which is available in BPS publication data entitled South Kalimantan in Figures.The results of the study show that, (1) Local Revenue, General Allocation Funds, Profit Sharing Funds, and Fiscal Stress have an affect on the level of independence simultaneously; (2) Regional Original Income dan Profit Sharing Funds affect the Level of Independence; (3) General Allocation Funds and Fiscal Stress have no significant effect on the Level of Independence; and (4) Regional Original Income is the most dominant variable that affects the Level of Independence.Keywords: Regional Original Revenue, General Allocation Funds, Revenue Sharing Funds, Fiscal Stress, Level of Independence.